The impact of levamisole and alcohol on white matter microstructure in adult chronic cocaine users. (2nd March 2022) - Michels, Lars; Moisa, Marius; Stämpfli, Philipp; Hirsiger, Sarah; Baumgartner, Markus R.; Surbeck, Werner; Seifritz, Erich; Quednow, Boris B.
Abstract: Previous brain imaging studies with chronic cocaine users (CU) using diffusion tensor imaging (DTI) mostly focused on fractional anisotropy to investigate white matter (WM) integrity. However, a quantitative interpretation of fractional anisotropy (FA) alterations is often impeded by the inherent limitations of the underlying tensor model. A more fine‐grained measure of WM alterations could be achieved by measuring fibre density (FD). This study investigates this novel DTI metric comparing 23 chronic CU and 32 healthy subjects. Quantitative hair analysis was used to determine intensity of cocaine and levamisole exposure—a cocaine adulterant with putative WM neurotoxicity. We first assessed the impact of cocaine use, levamisole exposure and alcohol use on group differences in WM integrity. Compared with healthy controls, all models revealed cortical reductions of FA and FD in CU. At the within‐patient group level, we found that alcohol use and levamisole exposure exhibited regionally different FA and FD alterations than cocaine use. We found mostly negative correlations of tract‐based WM associated with levamisole and weekly alcohol use. Specifically, levamisole exposure was linked with stronger WM reductions in the corpus callosum than alcohol use. Cocaine use duration correlated negatively with FA and FD in some regions. Yet, most of these correlations did not survive a correction for multiple testing. Our results suggest that chronic cocaine use, levamisole exposure and alcohol use were all linked to significant WM impairments in CU. We conclude that FD could be a sensitive marker to detect the impact of the use of multiple substances on WM integrity in cocaine but also other substance use disorders. Abstract : Our results suggest that chronic cocaine use, levamisole exposure and alcohol use were all linked to significant WM impairments in chronic cocaine users. We further conclude that FD could be a sensitive marker to detect the impact of the use of multiple substances on white matter integrity in cocaine users.